Sacred monuments of ancient Saryarka and modern researches - Kukushkin, I.A.; Tishkin, A.A.; Dmitriev, E.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The accumulation of materials characterizing the sacral monuments of ancient Saryarka took decades. Places of spiritual attraction of the Bronze Age are marked by necropolises, which were often created around the large funerary structures of charismatic military leaders, spiritual leaders or rulers, combining secular and spiritual power. The most famous are Aksu-Ayuly II, Ortau II, Begazy, Buguly III, Sangyru, Aybas-Darasy. Due to large-scale researches of recent years, such burial grounds as Tanabai, Kyzyltau, Besoba, Sherubai I, Karazhartas, Shantimes have been studied by archaeological methods, which can rightly be attributed to the sacred centers of the Bronze Age. The chronological spectrum of research covers almost all of the 2nd millennium BC, emphasizing the sacred and cultural features of each period.
Ежелгі Сарыарқаның сакралды ескерткіштері жəне заманауи зерттеулер
Сакральные памятники древней Сарыарки и современные исследования
Keywords: necropolis; burial structure; the Bronze Age; sacral; mausoleum